جماليَّاتُ البِنَاءِ اللُّغَويِّ في البَسْمَلَةِ (قراءةٌ أسلوبيَّةٌ معاصرة) - العرشاني محسن محمد يحي (Journal of Amran University, 2024)
This research moves in the area of linguistic construction of the Basmala (i.e., by the name of Allah). Through its phonetic, morphological, and grammatical levels, which constitute the largest part of its linguistic architecture, relying on the data of modern linguistic studies and accurate distributional statistics. The research was divided into 10 sections. The introduction included an introduction to the research, its importance, its objectives, and the reasons for choosing it. As for the first, second, third, and fourth sections, the aesthetics of the phonetic and syllabic structure in the Basmalah were shown. In the fifth, sixth, and seventh sections, research was conducted on concluded with the most important results which obtained by this research.